Children road safety training with augmented reality (AR) [Demo] - Lugmayr, Artur; Tsang, J.; Hobs, W.; Williams, T.; Lim, C.; Teo, Y.; Farmer, M. (2017)
© 2017 International Ambient Media Association (iAMEA). All rights reserved. Children killed or seriously injured through road accidents can be avoided through an appropriate safety training. Through play and engagement children learn and understand hazards at i.e. railway stations, bus stops, crossings, school zones, train stations, footpaths, or while cycling. We developed a rapid prototype of an Augmented Reality (AR) safety training proof-of-concept demonstrator for a scaled real-world model of dangerous road hazards. Two scenarios have been picked to give children the possibility to apply, and acquire knowledge of road safety: 1. handling emergency situations and informing authorities; 2. correct behavior at a bus stop on arrival/departure of a bus. In this paper we discuss our design approach, outline the technical implementation of the system, and give a brief overview of our lessons learned.